Higher diet quality in university students is associated with higher academic achievement: a cross‐sectional study. Issue 3 (27th February 2019) - Whatnall, M. C.; Patterson, A. J.; Burrows, T. L.; Hutchesson, M. J.
Abstract: Background: Unhealthy diets are typical of university students and the effects may be wider reaching than health. The present study aimed to describe the association between dietary intake and academic achievement in a sample of Australian university students. Methods: A cross‐sectional analysis of data from an online survey of 278 students from the University of Newcastle (UON), Australia [mean (SD) age 26.9 (10.5) years; 70.9% female] was conducted. Dietary intake, in terms of diet quality score [Australian Recommended Food Score (ARFS)], including individual sub‐scales, and percentage energy per day from energy‐dense nutrient poor (EDNP) foods, including individual sub‐groups, was assessed using the validated Australian Eating Survey Food Frequency Questionnaire, and academic achievement was assessed as self‐reported grade point average (GPA). The association between GPA and dietary intake was explored using linear regression, with adjustment for socio‐demographic and student characteristics. Results: Higher GPA was associated with higher diet quality (ARFS) (β = 0.02, P  = 0.011), higher sub‐scale scores for vegetables (β = 0.03, P  = 0.026) and fruit (β = 0.05, P  = 0.029) and with lower percentage energy per day from EDNP foods overall (β = −0.01, P  = 0.047) and also from sweetened drinks (β = −0.06, P  < 0.001). Conclusions: The results of the present study demonstrate small associations between a healthier dietary intake and higher academic achievement, as well as vice versa. Given that the associations were small, they may not be particularly meaningful. However, this evidence could be used as a motivator for efforts aiming to improve dietary intake among university students.